WHAT A MARKETER NEEDS TO KNOW ABOUT THE METAVERSE - Bilyk, I. I.; Lavryk, K. R. (The actual problems of regional economy development, 2024)
The article explores the potential of the metaverse for marketers and provides a detailed understanding of this new digital space, analyzing its potential for marketers by focusing on the opportunities and challenges it brings. The metaverse is described as a combination of real and digital spaces, providing users with the ability to interact with digital objects and other users in real-time. The potential of the metaverse for marketers is discussed, and key aspects that marketers should consider in their strategies for utilizing the metaverse are identified. These aspects include defining marketing goals, platform selection, creating innovative experiences, experimenting with digital revenue models, collaborating with experts and industry companies, studying potential risks, and developing new metrics to measure marketing success. Marketing methods that can be used in the metaverse are discussed, such as augmented reality, future content, loyalty program enhancements, SEO, and search marketing. Innovative ways to complement digital marketing using the metaverse are described, including virtual stores, events, salons, educational guides, tourism, digital collecting, and expanding the influence of individuals. It is noted that the metaverse can become an effective tool for marketers to reach a wider audience, create engaging experiences for consumers, enhance personalization, and ensure economic efficiency. The potential challenges and opportunities of the metaverse for marketers are discussed, and specific examples of innovative strategies in this context are provided. A combination of general scientific and specialized research methods, including comprehensive analysis and synthesis of scientific works, thorough study of scientific publications, and monitoring of research on consumer interaction in the digital space of the metaverse, was used to conduct the study. The results of the research will help marketers understand the opportunities and challenges of the metaverse and develop strategies for successful use of this space to promote brands and engage audiences.